2007
DOI: 10.1080/09541440600758812
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory processes in language switching: Evidence from switching language-defined response sets

Abstract: We used language-defined response sets (digit names from 1 to 9 in different languages) to explore inhibitory processes in language switching. Subjects were required to switch between two (Experiment 1) or among three (Experiment 2) languages. In Experiment 1, we obtained a shift cost when subjects switched between their first and second language, between their first and third language, or between their second and third language. For each language pairing, the shift cost was larger for the relatively dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
343
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 250 publications
(383 citation statements)
references
References 23 publications
32
343
8
Order By: Relevance
“…Indeed, because L1 is the dominant language, stronger inhibitory processes are applied to L1 when responding in L2 than vice versa (e.g., Costa & Santesteban, 2004;Green, 1998;Meuter & Allport, 1999;Philipp & Koch, 2009;Philipp, Gade, & Koch, 2007). Furthermore, the difference between rounding down and rounding up grew larger when the Chinese had to answer in their second language.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, because L1 is the dominant language, stronger inhibitory processes are applied to L1 when responding in L2 than vice versa (e.g., Costa & Santesteban, 2004;Green, 1998;Meuter & Allport, 1999;Philipp & Koch, 2009;Philipp, Gade, & Koch, 2007). Furthermore, the difference between rounding down and rounding up grew larger when the Chinese had to answer in their second language.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been frequently reported that switch costs decrease with preparation time (e.g., Meiran et a!., 2000;Rogers & Monsell, 1995), but manipulations of preparation time had no significant impact on n-2 repetition costs under most conditions (Gade & Koch, 2008;Mayr & Keele, 2000;Schuch & Koch, 2003). Preparatory reductions of n-2 taskrepetition costs have been observed only in conditions that entail the opportunity of response preparation in addition to task preparation (e.g., for a simple-response task; Koch et aI., 2004) or when the task was a naming task with a relatively small stimulus set (Philipp, Gade, & Koch, 2007). More evidence for a dissociation of switch costs and n-2 task-repetition costs comes from fMRI and neuropsychological studies.…”
Section: Proactive Interference Of Tasksmentioning
confidence: 99%
“…As we have discussed earlier, AHport and Wylie (1999) assumed both positive and negative task priming. The idea of negative priming is particularly pertinent in the literature on bilingual switching, in which switch-cost asymmetries have been taken as a hallmark of inhibitory control of the mental lexicon (for discussion, see, e.g., Costa & Santesteban, 2004;Meuter & Allport, 1999;Philipp, Gade, & Koch, 2007;Philipp & Koch, 2009). Correspondingly, Yeung and MonseH (2003b) conceded that "it is likely that a complete model of task switching will need to incorporate inhibitory effects" (p. 468).…”
Section: Proactive Interference Of Tasksmentioning
confidence: 99%
“…Even highly proficient bilinguals usually have a dominant and a non-dominant language which is reflected, for instance, in faster picture-naming latencies for their first compared to their second language (e.g., Chen and Leung, 1989;Christoffels et al, 2006;Potter et al, 1984). However, under language switching conditions, this difference in naming latencies between L1 and L2 may disappear or even reverse, with shorter picture-naming latencies for the second than the first language (Costa and Santesteban, 2004;Costa et al, 2006;Meuter and Allport, 1999;Philipp et al, 2006; see also Kroll et al, 2006). Switching between languages may therefore profoundly affect production in the native tongue.…”
mentioning
confidence: 96%